PENGARUH E-FAKTUR DAN E-BILLING TERHADAP KEPATUHAN WAJIB PAJAK BADAN YANG TERDAFTAR DI KANTOR PALAYANAN PAJAK PRATAMA SUBULUSSALAM - DALIMUNTHE, MOHD IDRIS (UNIVERSITAS SARI MUTIARA INDONESIA, 2019)
The purpose of renewing the tax system with the addition of e-invoices is expected to increase tax compliance can also increase public confidence in tax administration and high employee tax productivity, the purpose of using information technology in taxation is to save time, easy, and accurate. The use of information technology in tax administration is expected to increase service for taxpayers, both in terms of quality and time so that it is more effective than the results of the study concluded the electronic Application variable tax invoice (E-invoice) has a positive and significant effect on corporate taxpayer compliance at the tax service pratama Subulussalam 2017. E-billing variable has a positive and significant effect on corporate taxpayer compliance at the preservice tax office of Subulussalam 2017. Application variable electronic tax invoices (e-invoices) and e-billing jointly have a significant effect towards Tax Compliance of entities registered in the pre-service office ofSubulussalam